#TITLE_ALTERNATIVE# - NUGRAHA HIDAYAT (NIM 15106024); Pembimbing: Dr. Irwan Meilano, ST, M.Sc., dan Irwan Gumilar, S, MARTA
Sunda Strait lies at the confluence of Eurasian plate and Indo-Australian plate. Sunda strait has a relatively high seismic activity that shown by several earthquakes that have occurred in the Sunda Strait region. The high seismic activity was caused by the subduction zone and tectonic faults in the Sunda Strait region. Faults that discussed in this undergraduate thesis are Semangka segment of Sumatera fault and continuation of Sumatera fault. Based on the high seismic activity in the Sunda Strait, it is necessary to do research on the strain that occurred in the Sunda Strait region to determine the tectonic activity in that area. Then do the seismic hazard analysis based on the two fault activity.